Uncovering Determinants of Discontinuous Intention of Attention to Mobile LINE-P Messages - Chiu, Hsin-Yi; Lin, Jia-Sing; Wu, Chien-Hsing (2018 5th International Conference on Behavioral, Economic, and Socio Cultural Computing (BESC), 2018)
The purpose of the research is to conduct a qualitative study based on the expectation-disconfirmation theory to conceptually explore the potential determinants of discontinuous intention of attention to Taiwan's mobile LINE-P messages. The research considers positive and negative determinants associated with use willingness. Based on the determinants, related concepts and research propositions are proposed for further empirical examination. Based on the data analysis from 22 subjects' interview, research results are obtained to derive six propositions. The research model according to the six propositions is presented and measure and sample are also delineated concisely for future empirical examination. The current research provides a grounded theory to describe the determinants of discontinuous intention of attention to LINE- P messages.